The Pandemic Impact on The Indian Economy - An Application of Garch Model - Vadivelu, Sakthirama; J, Jebastin Jerome Michelraj (Journal of Contemporary Research in Management (JCRM), 2023)
The world pandemic has witnessed a great recession impact in the year 2020 due to the outbreak of the coronavirus. Many countries were affected badly because of the pandemic. India has the second most infected cases in the world and the financial performance of different sectors in the country as well as the overall economic performance of the country is badly affected by the pandemic. The objective of this project is to assess how the pandemic has affected the performance of India’s key economic indicators, financial market performance, and the profitability of some of the important sectors in India. Our project makes use of macroeconomic indicators like GDP, GDP from different sectors, inflation rate, and daily infection data to analyze the impact of the pandemic on the Indian Economy. The macroeconomic variables are tested for stationarity using ADF tests and for heteroscedasticity using ARCH-LM tests and the GARCH model is applied to analyze the volatility of the indicators. The financial performance of most of the companies taken under study. Analysis shows that pandemic regulations have affected the volatility of GDP from most of the sectors and not affected the inflation rate and the stock market indices.